1989
DOI: 10.1007/bf01130729
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of follicular diameter with oocyte recovery and maturity at the time of transvaginal follicular aspiration

Abstract: Forty-four consecutive patients undergoing transvaginal follicular aspiration for in vitro fertilization underwent ultrasonic measurement of follicular diameter at the time of oocyte retrieval to determine the correlation of follicular size with recovery rates and oocyte maturity. Based on the results of 412 follicles aspirated, the data were grouped by size (less than or equal to 11, 12-14, 15-17, 18-20, and greater than or equal to 21 mm) and oocyte maturity. Recovery rates were significantly higher in 18- t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
30
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 7 publications
10
30
1
Order By: Relevance
“…In addition, the aspiration of follicles greater than 18 mm. provided the highest probability of retrieving mature oocytes (MII), confirming previous publications [2,3,6].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, the aspiration of follicles greater than 18 mm. provided the highest probability of retrieving mature oocytes (MII), confirming previous publications [2,3,6].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, at the time of retrieval, oocytes are collected from follicles of varying sizes, and this variation appears to coincide with a correlation between follicular size and stage of oocyte development and maturity. A positive correlation between follicular size and the presence of metaphase II oocytes has been reported [1,2]. In addition, previous literature has suggested that oocytes from follicles with a mean diameter greater than 12 mm have significantly higher fertilization and cleavage rates [3,4].…”
Section: Introductionmentioning
confidence: 92%
“…Many studies have demonstrated that the oocyte quality retrieved from large follicles is often better than that from small follicles [1][2][3], and those oocytes from large follicles tend to develop high quality embryos. Therefore, some clinicians argue that the timing of hCG triggering should be delayed to prolong the duration of ovarian stimulation and stimulate enough follicular growth.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the rationale for curetting the follicle to remove increased numbers of granulosa cells during retrieval to decrease the amount of VEGF release. The OHSS rate in our population was within previously reported ranges of moderate to severe OHSS of 2-5% [11,14,15]. Given these overall low OHSS rates, our study was insufficiently powered to detect a difference in the incidence of OHSS.…”
Section: Discussionmentioning
confidence: 52%
“…It is also important to note that there were no differences between the groups in the number of antral follicles or in the size of follicles on the day of hCG which are both major factors predicting oocyte yield [10] and maturity [11]. There was no difference in the number of germinal vesicles (immature oocytes) between the groups which we may expect to see with an increase total number of oocytes retrieved.…”
Section: Discussionmentioning
confidence: 90%